Implementasi Kebijakan Pemungutan Pajak Reklame Sesuai Perda Nomor 12 Tahun 2011 Tentang Pajak Reklame Dinas Pendapatan Daerah Jakarta Utara Tahun 2021 - Taryudi Taryudi; Irawati Irawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purpose of this research is to find out the Implementation of the Billboard Tax Collection Policy in accordance with Local Regulation Number 12 of 2011 concerning t he Billboard Tax of the North Jakarta Local Revenue Service in 2021 at Pademangan Local Tax Collection Service Unit. This research is a type of qualitative research using descriptive analysis. The results of this research indicate that the implementation of the billboard tax collection policy using George Edward III's theory which consists of 4 (four) dimensions including: the communication dimension there is still a lack of direct socialization to taxpayers; the dimension of resources consisting of human resources is still a lack of supervisory billboard tax officers; dimensions of financial resources have been met; the dimensions of the disposition of the implementor's response, understanding of the policy is still not met due to taxpayers who still do not understand the procedures for administering billboards; and the dimensions of the bureaucratic structure are still not met because the licensing process for the administration of billboards tends to be difficult and long, there was a violation regarding the installation location permit, the media for placing billboards that violated environmental ecology, there were installers who did not pay attention to the validity period of the permit for installing advertisements, so that many billboards were posted without confirmation of the extension of billboard installation. So that the efforts made in overcoming this are giving warning letters, issuing summons, submitting appeal letters, and forcibly dismantling billboards and improving the billboard administration procedure to make it easier and ease of the licensing process in order to facilitate the licensing process and meet their tax obligations in addition to the existence of fixed regulations for the billboard tax so that taxpayers more easily understand existing regulations.